2020
DOI: 10.1186/s12889-020-09085-7
|View full text |Cite
|
Sign up to set email alerts
|

Understanding mobility and sexual risk behaviour among women in fishing communities of Lake Victoria in East Africa: a qualitative study

Abstract: Background HIV-prevalence and incidence is high in many fishing communities around Lake Victoria in East Africa. In these settings, mobility among women is high and may contribute to increased risk of HIV infection and poor access to effective prevention and treatment services. Understanding the nature and patterns of this mobility is important for the design of interventions. We conducted an exploratory study to understand the nature and patterns of women’s mobility to inform the design of HIV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 42 publications
3
35
1
Order By: Relevance
“…Z. Kwena et al (2020) found in their research in Kenya, Tanzania and Uganda that women make circular trips between fish landing sites on Lake Victoria to buy and sell fish, and also visit families and their villages away from the lake. The size of the fishing business influenced the distance travelled and the amount of time away, with those operating on a larger scale travelling further and being away for longer than those with a medium-sized business.…”
Section: Gendered Migration Of Fisherfolkmentioning
confidence: 99%
See 3 more Smart Citations
“…Z. Kwena et al (2020) found in their research in Kenya, Tanzania and Uganda that women make circular trips between fish landing sites on Lake Victoria to buy and sell fish, and also visit families and their villages away from the lake. The size of the fishing business influenced the distance travelled and the amount of time away, with those operating on a larger scale travelling further and being away for longer than those with a medium-sized business.…”
Section: Gendered Migration Of Fisherfolkmentioning
confidence: 99%
“…Women also generated income by cooking and renting out rooms at the landing sites, a particularly important service for migrant fishers (Z. Kwena et al, 2020). In the Dagaa fishing camps in Tanzania, many of the women who were working as cooks were either widowed or divorced (Medard, 2015).…”
Section: Gendered Relations Within Fisheriesmentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, despite the crucial social and financial roles of women in the artisanal and small‐scale fishing communities, they often constitute lower strata of the workforce and are often underpaid (CSE, 2016; Ogden, 2017). Also, due to economic vulnerability, the women in the SSF communities are susceptible to issues such as lack of sanitation and health services, prevalence of drug and alcohol abuse, and sexual exploitation (Bennett et al., 2020; Kwena et al., 2020; Woodhead et al., 2018). Unfortunately, there are yet no data on exact implications of the COVID‐19 pandemic on the situation of the women involved in the SSF or the entire aquaculture and fishing industry.…”
Section: Effect Of Covid‐19 On Ssfs and Artisanal Fishersmentioning
confidence: 99%